The Caribbean multilingual, multidimensional and multicultural identities - Townsel, Sylviane (2008)
Focuses on the different facets that make the Caribbean islands, small but important in their multilingual, multidimensional and multicultural identities. Views the history of the Caribbean as it manifested itself some decades ago, and underlines the rapid changes undergone in these islands.